CRITICAL ANALYSIS OF THE IMPLEMENTATION OF THE MARKET DAY PROGRAM IN FOSTERING THE ENTREPRENEURIAL SPIRIT AMONG STUDENTS IN ELEMENTARY SCHOOL - Iriyani, Muji; Andriani, Ana (Universitas Muhammadiyah Purwokerto, 2024)
Education is one way to build an entrepreneurial spirit. One of the entrepreneurship programs is the market day program. The purpose of this study is to analyze the implementation of the market day program in fostering the entrepreneurial spirit of students at SD Negeri 1 Banjarkulon Banjarnegara. This research method uses a descriptive qualitative approach with a case study method. Data collection techniques using observation, interviews and documentation. The sources of informants used are students, teachers managing the market day program and parents of students The results of this study indicate that with the market day program most students have an entrepreneurial spirit such as self-confidence, creativity in making products, enthusiasm in selling, having a leadership spirit and taking risks. The conclusion of this study is that the implementation of the market day program at Â SD Negeri 1 Banjarkulon Banjarnegara can foster the entrepreneurial spirit of students well.